Pengembangan Kompetensi Profesional Guru Melalui Diklat Penelitian Tindakan Kelas Di Kemenag Kabupaten Jepara - Ratna Hartati (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2017)
This is the experimental research to found the pattern of implementing by giving the pretest for the participants ofaction research teachers in the Training and Education before the implementation of training. The participants are given the knowledge that is related to the action research. The posttest is given after implementation of training as the last activity.Â Population and sample of this research are the teachers of The Islamic Religion Learning for Elementary School, Intermediate School, High School and Technical School in the Jepara Regency of Religion Ministry as partisipant, that is took by random. The result shown significant increase ofthe low criteria bythe pretest and postest from 9 (30 %) participants, became 0 (0 %) participants. For the medium criteria from 18 (60 %) participants, became 6 (20 %) participants, and for the high criteria from 3 (10 %) participants, became 24 (80 %) participants. This study concludes that according to data, the implementation of the Training and Education of action research in the Regency was able to improve the understanding to write about action research for teachers of Islamic Religion Learning.Keywords :Â Understanding, Action Research, Training